Hospital Pharmacy Information Systems Evaluation Framework: A Systematic Review - Ken Inayati Latifa; Lutfan Lazuardi; Chairun Wiedyaningsih (Faculty of Medicine, Diponegoro University, 2026)
Hospital pharmacy information system is an application of an information system designed to support clinical pharmacy services oriented towards patient care, drugs provision and drug management. In the implementation of pharmacy information systems, evaluation is needed to assess the extent to which the information system is beneficial. The purpose of this systematic review is to determine the methods of hospital SIF evaluation framework. This systematic review followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. The article search used Scopus, and Google Scholar databases from 2014 to 2024, taking into account the eligibility and inclusion criteria. eligibility and inclusion criteria. In this Systematic review, 7 articles were obtained included in the study. No evaluation framework was developed specifically for SIF evaluation. There were 4 evaluation methods used is to evaluate systems such as, HOT FIT, EUCS, TAM, Delone and Mclean. The most widely used method is HOT FIT with 3 articles. Evaluation of hospital information systems is important to ensure the they function effectively and efficiently while meeting the needs of hospital services. The evaluation results serve as a basis for system improvement and development, enabling the hospitals to provide high-quality healthcare services.